Organizational barriers associated with the implementation of national essential medicines policy: A cross-sectional study of township hospitals in China. (November 2015) - Yang, Lianping; Liu, Chaojie; Ferrier, J. Adamm; Zhang, Xinping
Abstract: This study identifies potential organizational barriers associated with the implementation of the Chinese National Essential Medicines Policy (NEMP) in rural primary health care institutions. We used a multistage sampling strategy to select 90 township hospitals from six provinces, two from each of eastern, middle, and western China. Data relating to eight core NEMP indicators and institutional characteristics were collected from January to September 2011, using a questionnaire. Prescription-associated indicators were calculated from 9000 outpatient prescriptions selected at random. We categorized the eight NEMP indicators using an exploratory factor analysis, and performed linear regressions to determine the association between the factor scores and institution-level characteristics. The results identified three main factors. Overall, low levels of expenditure of medicines (F1) and poor performance in rational use of medicines (F2) were evident. The availability of medicines (F3) varied significantly across both hospitals and regions. Factor scores had no significant relationship with hospital size (in terms of number of beds and health workers); however, they were associated with revenue and structure of the hospital, patient service load, and support for health workers. Regression analyses showed that public finance per health worker was negatively associated with the availability of medicines ( p < 0.05), remuneration of prescribers was positively associated with higher performance in the rational use of medicines ( p < 0.05), and drug sales were negatively associated with higher levels of drug expenditure ( p < 0.01). In conclusion, irrational use of medicines remains a serious issue, although the financial barriers for gaining access to essential medicines may be less for prescribers and consumers. Limited public finance from local governments may reduce medicine stock lines of township hospitals and lead them to seek alternative sources of income, jeopardizing their capacity to meet the needs of local consumers. Highlights: The NEMP implementation faces significant organizational barriers in China. Expenditure may be effectively reduced for patients regarding access to medicines. The irrational use of medicines remains serious. Limited public finance may encourage township hospitals to reduce medicine stock lines.